ChemInform Abstract: Luminescence Properties of Red‐Emitting Ca9Y(PO4)7:Eu3+ Phosphor for NUV White‐LEDs. Issue 3 (21st January 2014) - Wang, Baoling; Lin, Yiting; Ju, Haidong
Abstract Ca9Y(PO4)7:Eu3+ phosphors are prepared by solid state reaction of stoichiometric amounts of CaCO3, (NH4)2HPO4, Y2O3, and Eu2O3 (calcination in air, ≥1100 °C, 5 h).